The end of the middle class? The development of the income distribution in Austria and Europe - Kranzinger, Stefan; Derndorfer, Judith (Momentum Quarterly, 2016)
Recently, there has been a spate of interest in the hollowing out of the middle class. This paper examines how three different income groups, in particular the middle class, have fared in 20 European countries. The research is based on EU-SILC data starting from 2004 up to 2012 and uses disposable equalized household income. At European level, we aim to identify whether countries belonging to the same welfare state regime develop similarly with regard to their income distribution. At country level, a special interest lies in Austria. Here household structure according to income groups and the consequences of the economic and financial crisis are dealt with. The results indicate that within conservative, liberal and post-socialist welfare state regimes similar developments are observed. The study further shows that in slightly more than half of all analyzed countries the share of middle class households increased. In Austria, however, the middle class decreased by -4,2 %.
Keywords: Middle Class; Income Distribution; Austria; EU-SILC